2006
DOI: 10.1124/dmd.106.011627
|View full text |Cite
|
Sign up to set email alerts
|

Rat Cytochrome P450 2C11 in Liver Microsomes Involved in Oxidation of Anesthetic Agent Propofol and Deactivated by Prior Treatment with Propofol

Abstract: ABSTRACT:Propofol (2,6-diisopropylphenol) is a widely-used anesthetic agent attributable to its rapid biotransformation. Liver microsomal cytochrome P450 (P450) isoforms involved in the biotransformation of propofol in rats and the effects of propofol in vivo on P450 levels in rats were investigated. Of six cDNA-expressed rat P450 isoforms tested, CYP2B1 and CYP2C11 had high catalytic activities from 5 M and 20 M propofol concentrations, respectively. Rates of propofol metabolism, at a substrate concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Typical P450 substrates, their reaction products, and other reagents used in this study were obtained from sources described previously or were of the highest quality commercially available. 24,26) Typical P450-dependent marker oxidation activities were measured in liver microsomes in rats to evaluate enzyme inductions on treatment with DDT. Activities for the O-dealkylation of ethoxyresorufin (20 µM, for P450 1A) and pentoxyresorufin (100 µM, P450 2B) and for testosterone 7α-hydroxylation (200 µM, P450 2A), tolbutamide methyl hydroxylation (1000 µM, P450 2C), bufuralol 1 -hydroxylation (20 µM, P450 2D), chlorzoxazone 6-hydroxylation (50 µM, P450 2E), and midazolam 1 -and 4-hydroxylation (100 µM, P450 3A) were assayed according to the described HPLC methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Typical P450 substrates, their reaction products, and other reagents used in this study were obtained from sources described previously or were of the highest quality commercially available. 24,26) Typical P450-dependent marker oxidation activities were measured in liver microsomes in rats to evaluate enzyme inductions on treatment with DDT. Activities for the O-dealkylation of ethoxyresorufin (20 µM, for P450 1A) and pentoxyresorufin (100 µM, P450 2B) and for testosterone 7α-hydroxylation (200 µM, P450 2A), tolbutamide methyl hydroxylation (1000 µM, P450 2C), bufuralol 1 -hydroxylation (20 µM, P450 2D), chlorzoxazone 6-hydroxylation (50 µM, P450 2E), and midazolam 1 -and 4-hydroxylation (100 µM, P450 3A) were assayed according to the described HPLC methods.…”
Section: Methodsmentioning
confidence: 99%
“…Liver microsomes from male rats (7 weeks old) treated with DDT (10 mg/kg) and from untreated controls were prepared as described previously. 24) Microsomal P450 contents were determined spectrally by the established method. 25) Protein concentrations were estimated by using a bicinchoninic acid (BCA) protein assay kit (Pierce, Rockford, IL, U.S.A.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An aliquot of the supernatant after filter treatment (Millex-LG, 0.20μm, Millipore, Tokyo, Japan) was injected onto an analytical C 18 reversed-phase column (150 mm × 4.6 mm, Capcell Pak C 18 UG120 S5, Shiseido, Tokyo, Japan) maintained at 30°C. The mobile phase was 55% (v/v) acetonitrile at a flow rate of 0.6 mL/ min 20) . The elution profiles of propofol were monitored fluorometrically at an excitation wavelength of 270nm and an emission wavelength of 310 nm.…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…Genetic polymorphisms in CYP2B6 and UGT1A9 have been reported, along with their allele frequency in the Japanese population [8][9][10] . Several studies have shown that the allele frequency of the G516T mutation of CYP2B6 was approximately 20%, and the variation among genetic polymorphisms decreased the enzyme activity of CYP2B6 8) [10][11][12] . In contrast, Saito Y et al and Girard H et al have reported that the allele frequency of the I399C>T mutation of UGT1A9 was approximately 64% and that the variant increased the conjugation activity of propofol 9)13) .…”
Section: Introductionmentioning
confidence: 99%